Synthesis and structure of a complex of copper(I) with l-cysteine and chloride ions containing Cu(12)S(6) nanoclusters - Gizatullin, Amir (Acta Crystallogr E Crystallogr Commun, 2021)
The title hydrated copper(I)–l-cysteine–chloride complex has a polymeric structure of composition {[Cu(16)(CysH(2))(6)Cl(16)]·xH(2)O}(n) [CysH(2) = HO(2)CCH(NH(3) (+))CH(2)S(−) or C(3)H(7)NO(2)S], namely, poly[[tetra-μ(3)-chlorido-deca-μ(2)-chlorido-dichloridohexakis(μ(4)-l-cysteinato)hexadecacopper] polyhydrate]. The copper atoms are linked by thiolate groups to form Cu(12)S(6) nanoclusters that take the form of a tetrakis cuboctahedron, made up of a Cu(12) cubo-octahedral subunit that is augmented by six sulfur atoms that are located symmetrically atop of each of the Cu(4) square units of the Cu(12) cubo-octahedron. The six S atoms thus form an octahedral subunit themselves. The exterior of the Cu(12)S(6) sphere is decorated by chloride ions and trichlorocuprate units. Three chloride ions are coordinated in an irregular fashion to trigonal Cu(3) subunits of the nanocluster, and four trigonal CuCl(3) units are bonded via each of their chloride ions to a copper ion on the Cu(12)S(6) sphere. The trigonal CuCl(3) units are linked via Cu(2)Cl(2) bridges covalently connected to equivalent units in neighboring nanoclusters. Four such connections are arranged in a tetrahedral fashion, thus creating an infinite diamond-like net of Cu(12)S(6)Cl(4)(CuCl(3))(4) nanoclusters. The network thus formed results in large channels occupied by solvent molecules that are mostly too ill-defined to model. The content of the voids, believed to be water molecules, was accounted for via reverse Fourier-transform methods using the SQUEEZE algorithm [Spek (2015 ▸). Acta Cryst. C71, 9–18]. The protonated amino groups of the cysteine ligands are directed away from the sphere, forming N—H⋯Cl hydrogen bonds with chloride-ion acceptors of their cluster. The protonated carboxy groups point outwards and presumably form O—H⋯O hydrogen bonds with the unresolved water molecules of the solvent channels. Disorder is observed in one of the two crystallographically unique [Cu(16)(CysH(2))(6)Cl(16)] segments for three of the six cysteine anions.